Portuguese cooperation on basic education in Guine-Bissau - Carvalho, C.; Barreto, M. (Conferências do Centro Cultural Português, 2018)
Portuguese cooperation on basic education in Guine-Bissau. Presentation at the Portuguese Cultural Center, Bissau, Guiné-Bissau, February